Regional investment aid in Poland and Czechia - Wróblewska, Dominika (Review of European and Comparative Law, 2022)
The European Commission aims to ensure the transparency of aid granted by individual member states, and the simplest and most transparent instrument of support, next to grants, are tax relief. In both Czechia and Poland, investment incentives for new investments include regional aid in the form of tax relief in income tax – this includes income tax exemptions in Poland, and income tax relief in Czechia, as well as property tax exemptions in both countries. The purpose of this article is to compare the scope and conditions for receiving regional investment aid by entrepreneurs in these countries.